KiKli Fit: Investigating the Implementation of a Physical Activity Program in Pediatric Cancer - Lars Rehbein; Ann Christin Schneider; Christina Hillebrech; Christina Schindera; Amika Singh; Katharina Eva; Valentin Benzing (Current Issues in Sport Science)
Introduction Growing evidence in pediatric oncology underscores the significant benefits of physical activity (PA) during and after treatment (Benzing et al., 2021, 2022; Wurz et al., 2021). However, physical activity promotion in acute care settings within Swiss pediatric oncology units remains underdeveloped. To address this gap, the KiKli Fit program was developed and implemented at the Department of Pediatric Oncology and Hematology at the University Hospital Bern over the last 1.5 years. The aim of this research project was to accompany this process with implementation research to evaluate and support the integration of the developed PA program into clinical practice.